2014
DOI: 10.1017/s0950268813003324
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and control of H7 avian influenza viruses in birds and humans

Abstract: The H7 subtype HA gene has been found in combination with all nine NA subtype genes. Most exhibit low pathogenicity and only rarely high pathogenicity in poultry (and humans). During the past few years infections of poultry and humans with H7 subtypes have increased markedly. This review summarizes the emergence of avian influenza virus H7 subtypes in birds and humans, and the possibilities of its control in poultry. All H7Nx combinations were reported from wild birds, the natural reservoir of the virus. Geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
58
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 245 publications
(350 reference statements)
0
58
0
1
Order By: Relevance
“…Except viruses of the N1 and N8 subtypes in group 1, all NA subtypes that have infected humans belong to group 2. Of note, N2, N3, N7, and N9 were first found in combination with the H7 subtype in humans and caused mild to severe conjunctive and respiratory symptoms (27,34,35). Most cases of human infection with H7N2, H7N3, and H7N7 viruses have been related to poultry exposure, with limited evidence of sustained human-to-human transmission, and nearly all patients have recovered after antiviral treatment (35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Except viruses of the N1 and N8 subtypes in group 1, all NA subtypes that have infected humans belong to group 2. Of note, N2, N3, N7, and N9 were first found in combination with the H7 subtype in humans and caused mild to severe conjunctive and respiratory symptoms (27,34,35). Most cases of human infection with H7N2, H7N3, and H7N7 viruses have been related to poultry exposure, with limited evidence of sustained human-to-human transmission, and nearly all patients have recovered after antiviral treatment (35).…”
mentioning
confidence: 99%
“…Of note, N2, N3, N7, and N9 were first found in combination with the H7 subtype in humans and caused mild to severe conjunctive and respiratory symptoms (27,34,35). Most cases of human infection with H7N2, H7N3, and H7N7 viruses have been related to poultry exposure, with limited evidence of sustained human-to-human transmission, and nearly all patients have recovered after antiviral treatment (35). However, H7N9 is emerging in China, with more than 70% of infected people having influenza-like illness and rapidly progressive respiratory disorders (34,36).…”
mentioning
confidence: 99%
“…Han et al [13] analyzed the relationship between Human infections with avian influenza A(H7N9) virus in Huzhou city and the exposure of live poultry, and found that there was an obvious epidemiological link between them. In addition, the closure of live poultry markets and the suspension of live poultry trading were effective measures to control the spread of the H7N9 virus in the high-incidence areas, which could significantly reduce the incidence of outbreaks [2], and the live poultry markets infected by H7N9 virus were the most likely source of the epidemic [4,6,10].…”
Section: Research Status Analysesmentioning
confidence: 99%
“…ow-pathogenic (LP) avian influenza A viruses (AIVs) of the H5 and H7 subtypes in wild avian species are unique compared to the other 14 AIV subtypes, as they can become highly pathogenic and infect both poultry and mammalian species, including humans, seals, swine, and horses (1)(2)(3)(4)(5). The first studied AIV was an H7 virus originally described by Perroncito in northern Italy in 1878 as "fowl plague" (6).…”
mentioning
confidence: 99%
“…Most human H7 influenza A virus infections have been associated with poultry contact (1). Therefore, in the event of a large-scale outbreak in poultry, increased human contact may be an important risk factor.…”
mentioning
confidence: 99%